Avaliação dos efeitos de doses de triadimenol e de tebuconazole sobre o crescimento do mesocótilo em plântulas de trigo - Cavariani, Cláudio [UNESP]; Velini, Edivaldo Domingues [UNESP]; Bicudo, Silvio José [UNESP]; Nakagawa, J. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
Wheat (Triticum aestivum L.), Anahuac cultivar, were treated with six triadimenol (0,0; 12,5; 25,0; 37,5; 50,0 and 62,5 g of a.i./100 kg of seeds) and tebuconazole (0,0; 7,5; 15,0; 22,5 30,0 and 37,5 g of a.i./100 kg of seeds) dosis to reduce the subcrown internode length and then to deep the point of emission of adventitious roots. Seeds were seeded in pots with soil, with 5 cm of depth and after two weeks the seedlings number was counted and the subcrown internode length (CM) was evaluated. The CM may be represented by the equations: a) CM = 4,49 - 0,1779 x + 0,002161 x2 (r2 = 0,9247); b) CM = 4,62 - 0,29948 y + 0,006480 y3 - 0,00004622 y3 (r2 = 0,9551), where ''x'' and ''y'' represent tebuconazole and triadimenol dosis, respectively. The CM showed minimum values for triadimenol dosis equal to or higher than 37,5 g a.i./100 kg of seeds and for tebuconazole decreased continuously with the increase of the product dosis, showing values near to 1 cm for the maximum dosis. The triadimenol allowed, at suitable dosis, almost total inhibition of the wheat seedlings subcrown internode with no effects on seedling emergence and initial growth.

Sementes de trigo Triticum aestivum L., cv. Anahuac, foram tratadas com seis doses de triadimenol (0,0; 12,5; 25,0; 37,5; 50,0 e 62,5 g de i.a./100 kg de sementes) a de tebuconazole (0,0; 7,5; 15,0; 22,5; 30,0 e 37,5 g de i.a./100 kg de sementes), visando reduzir o comprimento do mesocótilo das plântulas, e, conseqüentemente, aprofundar no solo o ponto de emissão das raízes secundárias. As sementes foram semeadas em vasos, a cinco cm de profundidade, e após duas semanas contou-se o número de plântulas por vaso e avaliou-se o comprimento do mesocótilo (CM). Este pode ser representado pelas equações: a) CM = 4,49 - 0,1779x + 0,002161 x2 (r2 = 0,9247); b) CM = 4,62 - 0,29948 y + 0,006480 y2 - 0,00004622 y3 (r2 = 0,9551), onde "x" e "y" representam as doses de tebuconazole e triadimenol, respectivamente. O CM assumiu valores mínimos em relação a doses de triadimenol iguais ou superiores a 37,5 g de i.a./100 kg de sementes, enquanto que para o tebuconazole decresceu continuamente com o aumento da dose do produto, tendo apresentado valores próximos a 1 cm em relação à maior dose. O triadimenol permitiu, em doses adequadas, inibição quase total do mesocótilo das plântulas de trigo, sem lhe afetar a emergência ou o desenvolvimento inicial.
Effects of triadimenol and tebuconazole on a wheat seedlings subcrown internode growth
Keywords: TRITICUM-AESTIVUM; CULTIVAR; SEEDS; ROOTS